Comparison of apical sealing and periapical extrusion of the ThermaFil obturation technique with and without MTA as an apical barrier: An in vitro study - Satish Kumar; S J Deshpande; Ajay Singh Rao (Wolters Kluwer Medknow Publications, 2011)
Aim: The aim of the study was to compare the conventional ThermaFil obturation technique and ThermaFil obturation with mineral trioxide aggregate (MTA) as an apical barrier, with regard to apical sealing and extrusion. Materials and Methods: Twenty extracted human canines were instrumented using a crown-down technique and divided into two groups. The experimental group was obturated using ThermaFil obturation with MTA as an apical barrier and the control group was obturated using the conventional ThermaFil obturation technique. AH Plus sealer was used in both the groups. Apical extrusion was recorded. Teeth of both the groups were coated with nail polish, except for the apical 3 mm. After 24 h, they were suspended in black India ink for 48 h. Canines were decalcified, rendered transparent, and linear dye penetration was measured under ×40 stereomicroscope. Results: There was a significant extrusion noticed in conventional ThermaFil obturation technique. Frequency of extrusion of sealer and/or gutta-percha was supposed to be evaluated using χ² test, but since the values of the samples of ThermaFil plus MTA group were zero, statistical analysis could not be conducted, whereas linear dye leakage was calculated with Mann-Whitney U test because the distribution was abnormal. Conclusion: Although ThermaFil plus MTA group showed microleakage, extrusion of sealer and the core material was prevented in comparison with conventional ThermaFil obturation technique. It is advantageous to use MTA as an apical plug as there is no fear of apical extrusion and the root canal system can then be packed three dimensionally against this barrier using any thermoplasticized gutta-percha obturation technique.